The Potential of the Hybrid Course Vis-à-Vis Online and Traditional Courses - Brunner, Daniel L. (Teaching theology and religion, 2006)
Face-to-face, hybrid, and online courses are part of the panoply of course options available to students and teachers in the twenty-first century. This essay tackles the promise of hybrid courses for enhancing student learning in seminary contexts. The author contends that the introduction of hybrid instruction prompts faculty to revisit questions about pedagogy and improves student learning.